2021
DOI: 10.3390/ijms22115868
|View full text |Cite
|
Sign up to set email alerts
|

PDS5A and PDS5B in Cohesin Function and Human Disease

Abstract: Precocious dissociation of sisters 5 (PDS5) is an associate protein of cohesin that is conserved from yeast to humans. It acts as a regulator of the cohesin complex and plays important roles in various cellular processes, such as sister chromatid cohesion, DNA damage repair, gene transcription, and DNA replication. Vertebrates have two paralogs of PDS5, PDS5A and PDS5B, which have redundant and unique roles in regulating cohesin functions. Herein, we discuss the molecular characteristics and functions of PDS5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 188 publications
(328 reference statements)
0
45
0
Order By: Relevance
“…PDS5A, a sister chromatid cohesion protein PDS homolog A, is responsible for unloading auxin from chromatin, while CDCA5 (sororin) is involved in establishing sister chromatid cohesion (SCC) ( 15 ). Alterations in PDS5A expression levels have been observed in breast, kidney, esophagus, stomach, liver and colon cancer ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…PDS5A, a sister chromatid cohesion protein PDS homolog A, is responsible for unloading auxin from chromatin, while CDCA5 (sororin) is involved in establishing sister chromatid cohesion (SCC) ( 15 ). Alterations in PDS5A expression levels have been observed in breast, kidney, esophagus, stomach, liver and colon cancer ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…STAG2 is the most frequently mutated in solid cancers [ 219 , 220 ], and in hematologic malignancies, genes including STAG1 , STAG2 , RAD21 , SMC1A , and SMC3 are frequently mutated [ 221 223 ]. Also, precocious dissociation of sisters 5 (PDS5) is an associated protein of cohesin complex [ 224 ]. It has been shown that PDS5B protein behaves as a tumour suppressor, as PDS5B gene expression level is reduced in gastric and colorectal cancers [ 225 ], and about 47% of breast cancer have low expression of PDS5B [ 226 ].…”
Section: Key Structural Elements Mediating 3d Chromatin Interactionsmentioning
confidence: 99%
“…Apart from its four core structural subunits, the cohesin complex also contains several accessory and regulatory subunits, including PDS5, WAPL, sororin, and the loading-complex-forming proteins, NIPBL and MAU2. In vertebrates, PDS5 (there are two isoforms: PDS5A and PDS5B) is essential for the dissociation of cohesin complexes from the chromosome arms in early mitosis [ 71 , 72 ]. Another cohesin cofactor subunit, called WAPL, associates with PDS5 and, similarly to PDS5, acts as a crucial protagonist in the removal of cohesin complexes during the prophase [ 73 , 74 ].…”
Section: The Cohesin Complex and Its Role In Chromosome Segregationmentioning
confidence: 99%
“…The removal of cohesin from chromosomes occurs in a two-step manner. Most cohesin complexes dissociate from the chromosome arms by a separase-independent pathway during prophase [ 89 ] which requires the activity of the kinases Aurora B and PLK1, as well as the cohesin subunit proteins WAPL and PDS5 [ 72 ]. Furthermore, the phosphorylation of sororin during mitosis causes its inability to antagonize WAPL binding to PDS5, which results in the association of WAPL with PDS5 and the subsequent removal of cohesin complexes from the arms of chromosomes [ 88 ].…”
Section: The Cohesin Complex and Its Role In Chromosome Segregationmentioning
confidence: 99%